The Beautiful Bridegroom by Dan Shore, όπερα σε μια πράξη - (:unkn) unknown (My University, 2023)
The Beautiful Bridegroom Dan Shore Όπερα σε μια πράξη

The Beautiful Bridegroom Dan Shore Opera in one act
The Beautiful Bridegroom by Dan Shore, opera in one act
Keywords: Όπερα; Opera